Containment and care? A qualitative interview study exploring police custody staff views about delivering brief alcohol interventions to heavy drinking arrestees. (1st November 2020) - McGovern, Ruth; Crowe, Lisa; Addison, Michelle; Hickman, Matthew; Kidger, Judi; McColl, Elaine; Newbury-Birch, Dot; Kaner, Eileen
Abstract: Heavy alcohol use and associated needs are prevalent amongst arrestees. The custody suite offers an opportunity to identify and intervene with this population. However, it is unclear whether functions of care can be effectively delivered within an environment of containment. This study aimed to examine custody staff experiences of screening and delivering brief alcohol interventions to heavy drinking arrestees. Qualitative interviews were conducted with 25 custody staff (detention officers and assessment, intervention and referral staff), involved in a pilot feasibility trial of alcohol screening and brief interventions in the police custody suite. We examined the tension between containment and care using concepts of role security and therapeutic commitment to guide our analysis. Our findings show that custody staff considered brief interventions to be legitimate in the custody suite setting, although there were differing views relating to which staff are best placed to deliver them. Detention officers reported vacillating therapeutic commitment to intervening with heavy drinking arrestees, compounded by some arrestees being perceived to be 'undeserving' of care. Tensions inherent in the need for 'containment' as well as 'care' must be addressed if brief alcohol interventions are to be implemented within the custody suite.